Natural and Artificial Reefs at Mar del Plata, Argentina - Isla, Federico Ignacio (2010)
Integrated coastal zone management techniques usually search the preferences of the owners of the coastal properties but without considering the beach users. Multipurpose artificial reefs are submerged structures built in order to diminish wave action, to modify breaker conditions, to protect the coast, and to increase marine biodiversity. Alternatives construction types are considered in relation to the surfing quality of the waves of Mar del Plata. Although detached emerged breakwaters and low-crested submerged structures have been successfully applied to protect beaches from breaking waves, the artificial surfing reefs can improve breaker conditions for recreational purposes. Both structures may increase sand accumulation at the beach if it is naturally available; if not the beaches should be artificially nourished. Based on knowledge of the littoral transport and the bottom composition of the Ensenada Mogotes, artificial submerged reefs, combined with nourishment efforts, are proposed to recover the beach called Los Acantilados. The surfing conditions can improve as a surplus to the stability of the rocky-sandy nearshore ecosystem.